(untitled) (Práxis Educativa, 2025)
The article is based on a series of biographical-narrative interviews with in-service teachers working in secondary schools in the Autonomous City of Buenos Aires, with the aim of understanding how they construct their professional identities. The analysis focuses on the processes of biographization through which they narrate their training trajectories and identify the critical moments and interpersonal bonds that shaped them. The analysis and findings are organized into two parts. The first classifies the pathways that led to initial teacher education along a spectrum ranging from those who chose teaching as a natural option to those who passed through other training spaces before arriving there. The second part focuses on the critical moments in these trajectories and on how the construction of bonds with professional referents plays a key role in orienting these paths. Keywords: Teacher professional identity. Mentor teachers. Biography.